Uptake of HIV testing in Burkina Faso: an assessment of individual and community-level determinants - Fati Kirakoya-Samadoulougou; Kévin Jean; Mathieu Maheu-Giroux (BMC, 2017)
Abstract Background Previous studies have highlighted a range of individual determinants associated with HIV testing but few have assessed the role of contextual factors. The objective of this paper is to examine the influence of both individual and community-level determinants of HIV testing uptake in Burkina Faso. Methods Using nationally representative cross-sectional data from the 2010 Demographic and Health Survey, the determinants of lifetime HIV testing were examined for sexually active women (n = 14,656) and men (n = 5680) using modified Poisson regression models. Results One third of women (36%; 95% Confidence Interval (CI): 33-37%) reported having ever been tested for HIV compared to a quarter of men (26%; 95% CI: 24-27%). For both genders, age, education, religious affiliation, household wealth, employment, media exposure, sexual behaviors, and HIV knowledge were associated with HIV testing. After adjustment, women living in communities where the following characteristics were higher than the median were more likely to report uptake of HIV testing: knowledge of where to access testing (Prevalence Ratio [PR] = 1.41; 95% CI: 1.34-1.48), willing to buy food from an infected vendor (PR = 2.06; 95% CI: 1.31-3.24), highest wealth quintiles (PR = 1.18; 95% CI: 1.10-1.27), not working year-round (PR = 0.90; 95% CI: 0.84-0.96), and high media exposure (PR = 1.11; 95% CI: 1.03-1.19). Men living in communities where the proportion of respondents were more educated (PR = 1.23; 95% CI: 1.07-1.41) than the median were more likely to be tested. Conclusions This study shed light on potential mechanisms through which HIV testing could be increased in Burkina Faso. Both individual and contextual factors should be considered to design effective strategies for scaling-up HIV testing.